Relationship to giving behavior breast milk with mastitis incidents in the working area of the Mongeudong community health center, Lhokseumawe city - Cut Linar; Hernita, Hernita (Jurnal EduHealth, 2024)
The target population in this study was postpartum mothers in the Mongeudong Community Health Center Working Area, Lhokseumawe City. Data analysis used chi square analysis. Results: the majority of respondents were aged 20-35 years as many as 21 people (70%), the majority of jobs were unemployed as many as 22 people (73.3%), the majority had secondary education as many as 15 people (50%). The optimal frequency of breastfeeding was 17 people (56.7 % ) and the non-optimal frequency was 13 people (43.3%). The majority did not experience mastitis as many as 22 mothers (73.3 % ). The relationship between the frequency of breastfeeding and the incidence of mastitis was found to have a value of p (0.010) < α (0.05), so Ha was accepted. Conclusion: there is a relationship between the frequency of breastfeeding and the incidence of mastitis in the Mongeudong Community Health Center Working Area, Lhokseumawe City